3x-(4x-4)=

Simple and best practice solution for 3x-(4x-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(4x-4)= equation:


Simplifying
3x + -1(4x + -4) = 0

Reorder the terms:
3x + -1(-4 + 4x) = 0
3x + (-4 * -1 + 4x * -1) = 0
3x + (4 + -4x) = 0

Reorder the terms:
4 + 3x + -4x = 0

Combine like terms: 3x + -4x = -1x
4 + -1x = 0

Solving
4 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -1x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -1x = 0 + -4
-1x = 0 + -4

Combine like terms: 0 + -4 = -4
-1x = -4

Divide each side by '-1'.
x = 4

Simplifying
x = 4

See similar equations:

| 4x+3(x-6)=4(x-3) | | 15s^2-34s+15= | | 1/4w-5=-3 | | 123+k=649 | | 14x+19x-8+1=-2x+1-8 | | 3-2i=-5 | | -y^2=6y+9 | | 5x-3x+12=x+8 | | x-54=2 | | (3x+1)(p-5)=0 | | x-54=2x | | 6-2(3x)-x= | | 6-2(3x-4)= | | 3(2+3x)=8(x-5) | | 18-5y+12+2y= | | a+10=43 | | 1/2z+7=10 | | 43-a=10 | | 6-2(3x-4)-x= | | .33x-1=.75x-6 | | 10(y+z)=2(3y+5) | | 3x-3=3x-5 | | ln(13*lnx)=-4 | | -2-3(4-x)+5x=6 | | 3x+2(5x+11)=9 | | 25=7m-3 | | (6x+1)(6x-9)= | | 10v^2+29v-21=0 | | 3m(4n+2-m)= | | 4y+8x-6=0 | | 3x-200=5000 | | 3*ln*2x=5 |

Equations solver categories